Kajian Penerapan Teknologi Pengendalian Penyakit pada Pembibitan Sengon di Bogor - Arif Ravi Wibowo; Suryo Wiyono; Anna Fariyanti (Institut Pertanian Bogor, 2022)
Sengon (Falcataria moluccana) cultivations still have to face threats from plant diseases. Diseases can be found in nurseries and plantation. Biological agents can be used to control various types of plant diseases and have various advantages. The use of biological agents in forestry plantations must consider the aspects of effectiveness and efficiency. This study aims to examine the effect of various treatment of control technology packages on the incidence of major diseases, and to determine the financial feasibility of various disease control technology packages for sengon in nurseries. The research was conducted through interviews to explore cultivation techniques and production costs. In addition, experiments were carried out on the application of various disease control strategies using commercial formulations of biological agents. The commercial formulations of biological agents used were Rhizomax, Primagrain, Trichowish, Kayabio, Bio-Hara Plus, and fungicide Dithane M-45 80 WP. There were two treatment packages of new technology that have an effect on increasing the growth of sengon at the beginning of growth stage, namely P1 (BioHara Plus and KayaBio) and P2 (Rhizomax and Primagrain) treatments. All treatments of the new technology package had no significant effect on increasing the survival rate and suppressing the incidence and severity of disease in sengon seedlings. All new technology package treatments can generate profits even though the value is smaller when compared to existing technology treatments. All the new technology package treatments have an R/C ratio of more than 1 so that they are feasible to be applied by farmers. Keywords: biological control, feasibility, plant diseases, nurseries, Falcataria moluccana